The Mediating Role of Psychological Capital between Motivational Orientations and Their Organizational Consequences - Rodríguez-Cifuentes, Francisco (Int J Environ Res Public Health, 2020)
Just as we can speak of different personality traits, it is also possible to identify distinct motivational traits, which may be related to a series of organizational consequences. In this sense, understanding how these traits are related to workers performance is fundamental. Specifically, the purpose of this study is to test the mediating role of psychological capital in the relationship between such traits and organizational citizenship behaviors and counterproductive work behaviors, which is expected to be more significant in the first case. The study was carried out using a panel design, with a sample group of Spanish employees aged over 40 (n = 741), in two waves (with a 4-month interval). The results support the hypothesis that psychological capital resources may play a mediating role in some of the relationships explored and that approach orientation traits are mainly related to a better performance, fostering organizational citizenship behaviors and diminishing counterproductive work behavior. The findings show that employees who develop their personal resources may have a positive impact on their organizations. The implications of this study for counseling practices are discussed.